Public Preferences In Choosing Fracture Treatment In Laucimba Village, Kabanjahe District - Juliani Simanjuntak; Fitri Handayani Siregar; Sri Muri Dasa Wardhani (PT. Padang Tekno Corp, 2025)
This study aims to determine the perceptions and reasons or factors underlying community preferences in choosing fracture treatment in Laucimba Village, Kabanjahe District. The study was conducted in Laucimba Village using a qualitative descriptive method, with data collection techniques including observation, in-depth interviews, and documentation. The results of the study indicate that traditional medicine has a more dominant positive perception compared to modern medicine, traditional medicine is considered more affordable in terms of cost, comfort, and a relatively faster healing process. Meanwhile, modern medicine is perceived as a more certain and safe treatment because it is supported by medical examinations and professional health workers, but some people consider this treatment expensive and high risk because it requires surgery. Community preferences are generally influenced by factors such as cost, distance and accessibility, personal experience, and the influence of family and social environment. Community decision-making in choosing fracture treatment is a rational action that is adjusted to conditions, needs, and beliefs